THE DETRIMENTAL EFFECTS OF PERSON-ORGANIZATION MISFIT ON CAREER SUCCESS: MEDIATING EFFECT OF STRAIN - Nayyah Aarsh Dar; Dr. Syed Zaheer Abbas Kazmi; Dr. Qlander Hayat (International Journal of Contemporary Issues in Social Sciences, 2023)
The present research aims to observe the effect of Person-organization Misfit on Career Success with Job Strain mediation. The research performed in the service industry focused on the banking sector in Pakistan. The present research carried a quantitative research design and for data collection it utilized a survey questionnaire. The data was gathered from 562 bank employees from Islamabad and Rawalpindi. The data was gathered with two-time lags on the basis of research objectives and research framework. The gathered data was analyzed through the SEM (Structural Equation Modelling) using IBM AMOS 24. The results revealed that bank employees suffering from the Person-organization Misfit are more inclined to Job Strain which leads towards the reduced Career Success. Furthermore, it also observed and considered that how Person-organization Misfit induces reduced levels of career success amongst individuals through Job Strain in the employees of banking sector. The findings stated that there is a significant relationship among Person-organization Misfit and Career Success. Moreover, Job Strain significantly mediated the relationship of Person-organization Misfit and Career Success. The current study contributes theoretically and provides a stepping stone for industrial implications. Theoretically, its contribution is in the person-environment fit theory as well as the relative deprivation theory through the development of a research model with their amalgamation. The implications at industrial level includes the human resource managers, practitioners, and industrial psychologists in processes of recruitment, selection, and designing the interventions in such a way through which the Person-environment Fit could be possibly achieved, and the adverse outcomes of Person-organization Misfit could be avoided.